Beyond the sugar tax: public acceptability of a comprehensive food policy bundle in urban Ghana - Kasim Abdulai; Emil Kafui Amenu; Portia Bangkuu; Ivan Addae-Mensah; Francis Adane; Abass Daudi (Frontiers in Nutrition, 2026)
Background The escalating burden of diet-related non-communicable diseases in Ghana has prompted the government to implement a 20% excise tax on sugar-sweetened beverages through the Excise Duty (Amendment) Act 1108 of 2023. While fiscal measures have garnered significant advocacy, public health experts emphasize the need for a “double-duty” policy bundle, including food marketing restrictions, front-of-pack warning labeling, and public food procurement policies. The problem is that public support for this broader bundle remains understudied in urban Ghana, risking implementation failure. Objective This study evaluated the prevalence and socio-political determinants of public support for a comprehensive suite of food environment policies among adults in the Cape Coast Metropolis, Ghana, and explored underlying motivations. Methods Convergent mixed-methods design. Cross-sectional survey of 450 adults (18–69 years) using multi-stage cluster sampling. Support measured via validated 5-point Likert scales. Twenty-four in-depth interviews provided qualitative depth. Results Support was highest for front-of-pack warning labeling (81.4%), followed by marketing restrictions (76.8%), the sugar-sweetened beverage tax (71.2%), and public procurement (65.6%). Perceived policy effectiveness (adjusted odds ratio = 3.45) and trust in the Ghana Health Service (adjusted odds ratio = 1.92) were the strongest predictors. Qualitative findings revealed that support for the tax increases significantly if revenues are ring-fenced for the National Health Insurance Scheme. Conclusion Policymakers should immediately prioritize front-of-pack warning labeling and marketing restrictions as highly acceptable “empowerment” policies, while simultaneously legislating transparent earmarking of sugar-sweetened beverage tax revenues for non-communicable disease treatment and prevention. Future research should test these policies post-implementation using longitudinal designs.